SISTEM PENGAKUTAN SAMPAH DI KOTA MEULABOH ANALISIS ANGGARAN BIAYA UPAH KERJA BERDASARKAN UKURAN PRODUKTIVITAS PEKERJA PADA PEKERJAAN PASANGAN DINDING BATU BATA - Zakia Zakia (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2017)
One important factor in construction projects is wages , which is required for the measurement of labor productivity which will assist the contractor in project planning improvements to get the budget costs . Productivity can be used as a parameter in determining the duration of the activity , the amount of labor and cost . The main issues to analyze or measure the value of productivity / hour / person every type of work in determining wages .Objective analysis of the cost of construction , NFPA 2007 is calculated back to the ISO 2008. Based on research on building projects Tarbiyah Islamic Madrasah ( MTI ) is obtained for the installation of brick work piece rate according to ISO 2007 is not better when compared to ISO 2008 with unit price details work SNI 2007 amounted to Rp . 9,997 , - / org / m2 and according to ISO 2008 was Rp . 14,247 , - / Org / m2 , if it 's a brick wall stucco work on the calculation of unit wage according to ISO 2007 (Rp . 8,415 , - / org / m2 ) was no better as well when compared to ISO 2008 was Rp . 11,950 , - / Org / m2. In the ceramic work according to ISO 2007 Rp.24.788 , - / org / m2 no better also than ISO 2008 Rp . 52,615 , - / Org / m2 . In a painting according to ISO 2007 Rp . 2,560 , - / Org / m2 . not better as well when compared to ISO 2008 Rp . 3,520 , - / Org / m2. Keywords : labor productivity , wall , brick , wages.